Government accountants' readiness for accrual accounting adoption in Jordan: critical success factors / Moawiah Awad Alghizzawi and Rosnia Masruki - Alghizzawi, Moawiah Awad; Masruki, Rosnia (Accounting Research Institute (ARI), 2020)
This study aimed to examine the critical success factors of government accountants' readiness for adoption of accrual accounting in Jordan. Based on 331 usable questionnaire survey received, data were analysed using the SPSS version 24. Results of multiple regression analysis demonstrated that human resource and information technology contribute significant and positively influences government accountants' readiness for adoption of accrual accounting. Independent sample t-test and one-way ANOVA were performed in this study to assess the mean difference of government accountants' readiness according to demographic attributes. The results demonstrated significant changes in the mean of the endogenous variable between groups of the demographic attributes including; gender, experience, education and specialization or background. This study not only contributes to expanding the literature concerning adoption of accrual accounting in the Jordanian context, but also provides meaningful guideline to the government of Jordan for adopting accrual accounting, as well as providing insights on the critical success factors in the adoption process.